Peningkatan Kemampuan Mendengarkan Siswa SMK Negeri 1 Air Putih Melalui Media Audio Visual - Parulian Sibuea; Nurul Ilmi (Journal on Education, 2023)
Learning English, there are four language components, including: listening, reading, writing, and speaking, where these four components are the main factors in teaching English as a foreign language. These components will develop students' communication skills either orally or in writing. This research was conducted using classroom action research in 5 meetings. 1 initial meeting is used for the initial ability test, then 4 meetings are used for the learning process which consists of two cycles of learning in the classroom. The population in this study were all students of class X KI SMK Negeri 1 Air Putih, totaling 36 people, consisting of 28 female students and 8 male students. 9 students have relatively good ability in listening to English, 22 students have medium ability, and 5 students have less ability. The results of this study were 1) from the initial data, almost all students scored below the KKM, then in the first cycle it decreased to 8 students and in the second cycle, all students' scores were above the standards set at the school; 2) from the initial average of 48 it rose to 63 in cycle I and in cycle II it rose to 79; 3) from the initial data there were no students who passed while in the first cycle there were more, namely 4 students and in the second cycle all students achieved completeness.